2005
DOI: 10.1073/pnas.0408771102
|View full text |Cite
|
Sign up to set email alerts
|

A Caenorhabditis elegans model of insulin resistance: Altered macronutrient storage and dauer formation in an OGT-1 knockout

Abstract: O-linked N-acetylglucosamine (O-GlcNAc) is an evolutionarily conserved modification of nuclear pore proteins, signaling kinases, and transcription factors. The O-GlcNAc transferase (OGT) catalyzing O-GlcNAc addition is essential in mammals and mediates the last step in a nutrient-sensing ''hexosamine-signaling pathway.'' This pathway may be deregulated in diabetes and neurodegenerative disease. To examine the function of O-GlcNAc in a genetically amenable organism, we describe a putative null allele of OGT in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
271
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 205 publications
(285 citation statements)
references
References 69 publications
10
271
2
2
Order By: Relevance
“…OGT is essential for embryonic stem cell viability and somatic cell function (O'Donnell et al 2004;Shafi et al 2000). Deletion of OGT in Arabidopsis (Jacobsen et al 1996), Drosophila (Sinclair et al 2009;Gambetta et al 2009), and mice is lethal (Shafi et al 2000), and leads to dauer phenotypes in Caenorhabditis elegans (Hanover et al 2005), suggesting that O-GlcNAc is essential for cellular homeostasis.…”
Section: O-glcnac Transferasementioning
confidence: 99%
“…OGT is essential for embryonic stem cell viability and somatic cell function (O'Donnell et al 2004;Shafi et al 2000). Deletion of OGT in Arabidopsis (Jacobsen et al 1996), Drosophila (Sinclair et al 2009;Gambetta et al 2009), and mice is lethal (Shafi et al 2000), and leads to dauer phenotypes in Caenorhabditis elegans (Hanover et al 2005), suggesting that O-GlcNAc is essential for cellular homeostasis.…”
Section: O-glcnac Transferasementioning
confidence: 99%
“…Overexpression of OGA induces a mitotic exit phenotype (46), suggesting that it too may perform essential functions. We originally identified C. elegans OGT (25) and have shown that knockouts of ogt-1 in the nematode, although viable and fertile, have effects on insulin-like signaling (25,26). Because of the linkage of the human OGA to insulin resistance, we have now examined the impact of a knockout of the C. elegans OGA gene, oga-1.…”
mentioning
confidence: 99%
“…The pathway is highly conserved in plants and animals and plays a key signaling function in Arabidopsis, where it impacts numerous pathways, including gibberellin signaling (18)(19)(20)(21)(22)(23)(24). We recently showed that the hexosamine-signaling pathway influences insulin-like signaling in C. elegans (25,26) and mice (17). In man, the hexosamine-signaling pathway has been implicated in both diabetes mellitus and neurodegeneration (1,2,17,27).…”
mentioning
confidence: 99%
See 2 more Smart Citations